2015
DOI: 10.12707/riv14057
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of patients with hypertensive crisis admitted to an emergency hospital

Abstract: Caracterização dos pacientes atendidos com crise hipertensiva num hospital de pronto socorro Characterisation of patients with hypertensive crisis admitted to an emergency hospital Características de los pacientes tratados de crisis hipertensiva en un hospital de emergencias

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…Headache, extremity weakness, and vomiting were the most frequent signs and symptoms reported by hypertensive emergency patients, whereas headache, chest pain, and dyspnea were the most frequent signs and symptoms among hypertensive urgency patients. These manifestations are similar to study reports from different parts of the world 14,18,23,25,30‐34 . In contrast to this finding, a study from France reported chest pain and dyspnea as the most frequently reported symptoms from hypertensive emergency patients 29 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Headache, extremity weakness, and vomiting were the most frequent signs and symptoms reported by hypertensive emergency patients, whereas headache, chest pain, and dyspnea were the most frequent signs and symptoms among hypertensive urgency patients. These manifestations are similar to study reports from different parts of the world 14,18,23,25,30‐34 . In contrast to this finding, a study from France reported chest pain and dyspnea as the most frequently reported symptoms from hypertensive emergency patients 29 .…”
Section: Discussionsupporting
confidence: 87%
“…These manifestations are similar to study reports from different parts of the world. 14,18,23,25,[30][31][32][33][34] In contrast to this finding, a study from France reported chest pain and dyspnea as the of Ethiopia, 35,36 and some of these examinations were also addressed in studies from USA, France, and Brazil, which emphasize the importance of test results and demand in primary care. 18,32,37 On the other hand, although some of the first-line treatment mea- showed that there was a significant difference in the decrement of median diastolic blood pressure between patients with and without previous history of admission (P = .005), and between hypertensive emergency and urgency patients (P = .010).…”
Section: Discussionmentioning
confidence: 99%